Bruno Latour in Pieces : An Intellectual Biography - Schmidgen, Henning (Book collections on Project MUSE., 2015)
"Bruno Latour is one of the major figures of contemporary thought. This book provides a comprehensive overview of the Latourian oeuvre, spanning from his early work in the sociology and anthropology of science to his recent philosophy of multiple "modes of existence.""--